Examining the use of social media in teaching and learning foreign languages and the impact on students’ speaking abilities - Hazaymeh, Wafa’ A.; Khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
This research explores an innovative application of social media platforms, particularly Instagram live streaming sessions and language courses on YouTube, to improve proficiency in speaking and grammar of foreign language undergraduates. It investigated the effects of various social media platforms on language competence and to evaluate the relevance of these platforms to language teaching. The study used a pretest-post-test experiment methodology with a sample size of 392 individuals, who were split into groupings: Control and Experimental. To compare the means of the speaking proficiency and grammatical proficiency scores, t-tests were used as an analytical method. The results indicated that the groups were not significantly different from one another on the pretest, which served as a baseline for the assessment. Nevertheless, the results of the post-test demonstrated a significant rise in the Experimental Group's grammar proficiency (mean = 74.38), supporting the first hypothesis, which states that learning a language through social media can improve one's grammar skills. Just as the control group showed no change in their speaking abilities, the experimental group showed a marked improvement, with a mean score that pointed to increased proficiency. This supports the second hypothesis, which states that social media usage is associated with an improvement in foreign language learners' speaking abilities. These results show that using YouTube and Instagram in language classes is an effective strategy, showing that it has real-world applications and inspiring teachers to be creative in their methods so that students learn languages more interestingly and engagingly.